2016
DOI: 10.5173/ceju.2016.792
|View full text |Cite
|
Sign up to set email alerts
|

Day care PNL using 'Santosh-PGI hemostatic seal' versus standard PNL: A randomized controlled study

Abstract: IntroductionTo compare the outcomes of tubeless day care PNL using hemostatic seal in the access tract versus standard PNL.Material and methodsIt was a prospective randomized controlled study. Cases were randomized to either the day care group with hemostatic seal (DCS) or the control group where patients were admitted and a nephrostomy tube was placed at the conclusion of surgery.ResultsA total of 180 cases were screened and out of these, 113 were included in the final analysis. The stone clearance rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Based on the inclusion and exclusion criteria, 14 RCTs [ 11 – 24 ] were finally included in our meta-analysis, and consisted of 576 patients who underwent tubeless PCNL and 572 patients who underwent standard PCNL. The process used for literature search and study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the inclusion and exclusion criteria, 14 RCTs [ 11 – 24 ] were finally included in our meta-analysis, and consisted of 576 patients who underwent tubeless PCNL and 572 patients who underwent standard PCNL. The process used for literature search and study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 . The studies included five RCTs [ 16 19 , 24 ] which compared total tubeless PCNL with standard PCNL and nine RCTs [ 11 – 15 , 20 23 ] which discussed partial tubeless PCNL. Table 1 shows the basic characteristics of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations